Nutritional and management strategies for sheep and goats - Scotten, Skyler Seth (Kansas State University, 2022)
Three studies were conducted to evaluate methods to improve small ruminant nutritional and management strategies. In Exp. 1, the effects of substituting grain sorghum in place of corn was evaluated in growing lamb diets. A total of 72 Rambouillet wethers (initially 33.9 ± 3.10 kg BW) were utilized in a completely randomized design and allotted to 1 of 4 dietary treatments over 35 d. Each pen contained 3 sheep and there were 6 pens per treatment. Dietary treatments included a corn-based control (42% corn/0% sorghum) or 10%, 20%, or 30% of sorghum replacing corn. All diets included titanium dioxide as an indigestible marker, and fecal samples were collected every 6 hr over a 3-day period at the end of the experiment for determination of total tract nutrient digestibility. There was no evidence (P > 0.05) that the inclusion of sorghum impacted any measured growth performance criteria. However, the higher price of sorghum at the time of the experiment led to lambs fed diets with 30% sorghum having a greater (P = 0.017) feed cost/lamb than the diets with lower concentrations of sorghum. Lambs fed increasing levels of sorghum had linearly improved (P < 0.05) apparent total tract digestibility of dry matter and organic matter, but there was no evidence of diet impacting the nutrient digestibility of crude protein, fiber, or ether extract. In conclusion, at least 20% sorghum can be used in place of corn without impacting feed cost or nutrient digestibility. Up to 30% sorghum can be fed to lambs without altering growth to target specialized markets, but with potential impacts to feed cost and dry matter digestibility. Next, in Exp. 2, the impact of varying oral anthelmintic treatments was evaluated on fecal egg count and growth performance of growing Spanish goats. A total of seventy-two intact male goats (Spanish, 25.17 ± 3.0 kg) were obtained from the same commercial grazing operation. Goats were weighed upon arrival and allocated to elevated pens in an indoor facility to balance body weight. Pens were randomly assigned one of four oral anthelmintic treatments in a completely randomized design, which were administered according to manufacturers’ recommendations on d 0. Anthelmintic treatment included: Control (no treatment administered); 2) moxidectin (0.40 mg/kg; Elanco Animal Health, Greenfield, IN); 3) fenbendazole (10.00 mg/kg; Merck Animal Health, Rahway, NJ); or 4) albendazole (20.00 mg/kg; Zoetis Animal Health, Parsippany, NH). There were 3 goats/pen and 6 pens/treatment. Feces were collected weekly, along with animal weights and feed disappearance to calculate reduction in fecal egg count from d 0, average daily gain, average daily feed intake, and feed efficiency. Data were analyzed using the GLIMMIX procedure of SAS v.9.4 (SAS Inst., Cary, NC). There was no evidence (P > 0.05) that treatment impacted any measured response criteria. Compared to the control, the addition of an anthelmintic, regardless of type, reduced (P < 0.05) Eimeria eggs on d 7 and total eggs on d 28. The results of this study showed limited efficacy of anthelmintics in Spanish goats; which is contrary to other studies. These results may have been impacted by all animals being housed in elevated pens with no exposure to dirt or feces. Additional research is therefore warranted to compare anthelmintic efficacy in more commercially relevant environments. Finally, in Exp. 3, the effect of increasing levels of crude protein (CP) by substituting SBM place of corn was evaluated in growing Easycare lambs. A total of 77 Easycare (Dorper × Katahdin × Romanov) lambs were fed one of three dietary treatments in a Latin square design with 7 replicate pens per treatment during three 28-d phases. Dietary treatments included a control (7.7% SBM/89.5% corn) or the control with 11.7% or 15.7% SBM at the expense of corn. At the end of each phase, fecal samples were collected from six lambs per pen and analyzed to determine nutrient digestibility. After phase 1, five male lambs per treatment with the weight closest to the median were slaughtered and carcass data collected. Lamb ADG was impacted (P = 0.0004) by a sex × SBM interaction, with wethers being fed 7.7% SBM having reduced (P < 0.05) ADG compared to all ewes or wethers being fed 11.7 or 15.7% SBM diets. Increasing levels of SBM linearly increased lamb BW and ADG but did not impact any other growth performance variable. Increasing levels of SBM also increased (P < 0.05) apparent total tract digestibility of dry matter, organic matter, crude protein, and ether extract, but not (P > 0.05) crude fiber. Finally, there was no evidence (P > 0.05) that dietary treatment impacted carcass characteristics. These results suggest that growing easy care castrated males benefit from adding at least 4% SBM in place of corn to increase dietary CP, and that additional research is warranted to evaluate longer-term impacts on cost and carcass composition. Collectively, these three experiments have increased our scientific understanding in small ruminant nutrition and management and have provided a basis from which to form better science-based recommendations for producers.
Keywords: Sheep nutrition; Goat parasite